Chemistry for matriculation semester 1 - Norbani Abdullah; Lok, W. F. (SAP Publications (M) Sdn Bhd, 2022)
Chemistry for Matriculation Semester 1 is an introductory book which provides an excellent way for students undertaking subject under the Matriculation Programme to understand key concepts, principles, facts and theories.